الهجرات الحضرمية الي شبه جزيرة الملايو : الخلفيات التاريخية و التحولات الناتجة - Abdul Rani Yaakob Al-Fatani,; Farid Mat Zin, (Penerbit Universiti Kebangsaan Malaysia, 2012)
Migration plays an important role in history especially in the convergence between civilization and descendants. Migration also created numerous nations and civilizations for centuries and some of them are not even known their existence in the world; because of that, migration has been acknowledged as an important element in history. With reference to the roles and importance of migration, it is a duy to reseach and find out the journey of migration in the history of the Malay Archipelago, especially the way of life and the results behind its. This reseach discussed the effects of migration upon the Malay community which started in Arab-Yemen-to the Malay world through the Indian Ocean by traders, merchants and Islamic travelers. The migration brought an impact on the Malay community where changes occurred in both social and culture of the society because of the positive relationship with Islam and the Arabs. The relationship between the Malay Archipelago and the Arab started with the migration of the Hadrami traders. The Malays and the Hadramis were on equal level and the Hadramis acknowledge the Malays and always thought Malays as their competitors. The migration happened in five main patterns involving the Hadramis to the Malay world where they brought with them their cultures and social elements that have an impact on the local society until today. Some of the effects were strong ties between the Arab and the Malays and existence of the Arab culture in our Malay community today.